First case of invasive squamous cell carcinoma in a stoma of a Monti ileovesicostomy - Reid, Stephen; Althunayan, Abdulaziz; Capolicchio, John-Paul; Brimo, Fadi; Kassouf, Wassim (Canadian Urological Association Journal, 2014)
We report a very rare case of invasive squamous cell carcinoma (SCC) in the abdominal stoma of a Monti ileovesicostomy. Our patient underwent an uncomplicated Monti ileovesicostomy at age 16 for a neurogenic bladder. She presented 10 years later with difficulty catheterizing the stoma. A biopsy of peristomal tissue showed moderately differentiated SCC. A cystoscopy did not reveal any bladder tumours or suspicious lesions. A computed tomography (CT) scan of the abdomen and pelvis did not demonstrate metastasis. The patient underwent a complete en bloc resection of the stomal site, the Monti, a partial cuff of bladder, and 2 loops of bowel that were adherent to the Monti. Final pathology revealed pure invasive SCC arising around the stoma and negative surgical margins. Six months later, a follow-up CT scan showed no evidence of malignancy, while a cystoscopy revealed a small erythematous area in the posterior bladder wall. Urinary cytology was positive for SCC. Transurethral resection of the erythematous lesion with random bladder biopsies showed SCC in situ in the erythematous lesion and right lateral bladder wall. Staging workup was negative. The patient subsequently underwent a radical cystectomy and ileal conduit diversion with bilateral pelvic lymph node dissection. Final pathology on cystectomy specimen was SCC in situ without evidence of invasive carcinoma. The patient has remained in remission at the 3-year follow-up.